2001
DOI: 10.1073/pnas.98.4.1817
|View full text |Cite
|
Sign up to set email alerts
|

p53 associates with and targets ΔNp63 into a protein degradation pathway

Abstract: A human p53 homologue, p63 (p40͞p51͞p73L͞CUSP) that maps to the chromosomal region 3q27-29 was found to produce a variety of transcripts that encode DNA-binding proteins with and without a trans-activation domain (TA-or ⌬N-, respectively). The p63 gene locus was found to be amplified in squamous cell carcinoma, and overexpression of ⌬Np63 (p40) led to increased growth of transformed cells in vitro and in vivo. Moreover, p63-null mice displayed abnormal epithelial development and germ-line human mutations were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
115
0
2

Year Published

2002
2002
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(128 citation statements)
references
References 36 publications
(66 reference statements)
10
115
0
2
Order By: Relevance
“…We further looked for a possible contribution of p21 (also called p21 WAF1 , p21 sdi1 , p21 cip1 and Ink4A) to cell cycle control, since its elevated expression is well known to induce cell cycle arrest and was shown to be transactivated by TAp51 isoforms, which in turn is inhibited by DN isoforms (Yang et al, 1998;Ratovitski et al, 2001). Unexpectedly, we found that neither exogenous expression of TAp51B nor DNp51B influenced p21 promoter activity in keratinocytes (Figure 4d).…”
Section: Inhibition Of Notch1 Induced Growth Arrest Of Immature Keratmentioning
confidence: 91%
See 1 more Smart Citation
“…We further looked for a possible contribution of p21 (also called p21 WAF1 , p21 sdi1 , p21 cip1 and Ink4A) to cell cycle control, since its elevated expression is well known to induce cell cycle arrest and was shown to be transactivated by TAp51 isoforms, which in turn is inhibited by DN isoforms (Yang et al, 1998;Ratovitski et al, 2001). Unexpectedly, we found that neither exogenous expression of TAp51B nor DNp51B influenced p21 promoter activity in keratinocytes (Figure 4d).…”
Section: Inhibition Of Notch1 Induced Growth Arrest Of Immature Keratmentioning
confidence: 91%
“…The use of distal promoter generates TAp51 isoforms with transactivation domain (TA domain) in their NH 2 -terminus, capable of transactivating various p53 responsive promoters. The use of the proximal promoter generates DNp51 isoforms with a short peptide substituting for the TA domain, which exert dominant-negative activity against TA isoforms and p53 (Yang et al, 1998;Hibi et al, 2000;Ratovitski et al, 2001;Patturajan et al, 2002;Stiewe et al, 2002;Wu et al, 2003). In addition, both isoforms undergo three alternative splicing events at the COOH-terminus generating six different isoforms (reviewed by Ikawa et al (1999); Yang and McKeon (2000); Mills (2006)).…”
mentioning
confidence: 99%
“…Subsequently, UV-B-irradiated cells with irreparable damage would promote p51 downregulation triggered by its phosphorylation (Papoutsaki et al, 2005;Westfall et al, 2005). Furthermore, p53 activated after the initial delay period following damage would promote DNp51B degradation (Ratovitski et al, 2001;Waltermann et al, 2003) and inhibits Akt activation (Stambolic et al, 2001), thereby eliminating cells with irreparable DNA damage by inducing apoptosis. This mechanism implies that mutation of p53 will not only make keratinocytes defective in p53-dependent apoptosis, but also will allow DNp51B to escape from p53-dependent degradation, leading to excess accumulation of DNp51B protein.…”
Section: P51-dependent Protection Of Uv-b-irradiated Keratinocytes Ismentioning
confidence: 99%
“…Since wild-type p53 protein mediates degradation of DNp63 in vitro (Ratovitski et al, 2001) and actually p53 mutations strongly relate to overexpression of DNp63 in squamous cell carcinoma (Hibi et al, 2000), we investigated the possible association of p53 status with impaired DNp63 expression in urothelial carcinoma. The p53 status was assessed by immunohistochemistry using the PAb1801 antibody (Esrig et al, 1993;Koga et al, 2000).…”
Section: Expression Of P63 Is Not Associated With P53 Statusmentioning
confidence: 99%